Judging the mental states of others: 'mindreading' in legal decision-making. (2nd January 2020) - Gregory, Daniel
ABSTRACT: Legal processes very often require judges and jurors to make determinations as to what mental states other individuals were in at a particular point in time, i.e., what they intended, believed, considered etc. However, there are two ways that one can try to determine what mental states another person was or is in. One is to apply the information that one has about human psychology in the way that one applies a theory. The other is to mentally pretend that one is in the same situation as the other individual and see what mental states one would have oneself, before attributing these to the other individual. I show that the two methods can lead to different conclusions in the same circumstances and urge that this is a very serious problem.